Hubungan antara Kematangan Emosi dengan Kecenderungan Psikosomatis pada Remaja Yang Tinggal di Pondok Pesantren (Jurusan Bimbingan dan Konseling Islam, 2019)
The research aims to find out the relationship between emotional maturity and psychosomatic tendencies on teenagers living in boarding schools. This research is a quantitative study of correlation using data collection techniques in the form of emotion maturity scale and psychosomatic tendency scale. Subject of research amounted to 86 students from the population number of 430 students Pondok Pesantren Al-Qur'an Sciences (PIQ) Singosari Malang. Data retrieval using simple random sampling technique. The data analysis technique used is a product moment analysis with a significance of 0.05. The results showed that there was a link between emotional maturity and psychosomatic tendencies in teenagers living in boarding schools with significance values of 0.001 < 0.05. In the table correlation there is a correlation coefficient value of-0343 which means the higher the maturity of emotions then the lower the psychosomatic tendencies, as well as vice versa, the lower the maturity of emotions then the higher the tendency Psychosomatic.